Practical Instructions for the 2018 ESC Guidelines for the diagnosis and management of syncope - Kenny, Rose (My University, 2018)
The literature on syncope and associated conditions can be confusing because of a lack of consistency. The meaning of some terms hasbecome obscured, and new terms were introduced to compete witholder, often equally adequate ones. Regional differences exist in theinterpretation of various words. This glossary is provided to clarify thenomenclature and improve consistency with the European Society ofCardiology (ESC) definitions of syncope and related concepts.
PUBLISHED
Keywords: Guidelines; Syncope; Carotid sinus massage; Cardiac pacing; Implantable cardioverter-defibrillator; Syncope unit; Emergency department; Tilt testing; Prolonged ECG monitoring; Electrophysiological study; Sudden cardiac death; Transient loss of consciousness; Vasovagal syncope; Reflex syncope; Orthostatic hypotension; Cardiac syncope; Ageing